Coated pre-lithium-silicon-oxygen negative electrode material as well as preparation method and application thereof

By forming a cladding structure of an interface stabilization layer and a hydrophobic layer on the preliminary silicon oxygen negative electrode material, the problem of excessive growth of silicon grains caused by high-temperature sintering is solved, and the cell cycle performance and structural stability of the material are significantly improved.

CN119581543AActive Publication Date: 2025-03-07HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411533653.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing coating method needs to be sintered at high temperature, resulting in excessive growth of silicon grains and volume expansion, which is not conducive to the long circulation of prelithiated silicon oxygen negative electrode materials.

Method used

The interface stabilization layer and hydrophobic layer are used to obtain the interface stabilization layer through the water-soluble polymer calcination process, and the hydrophobic material is coated by the supercritical fluid method to form a uniform hydrophobic layer to avoid high temperature sintering.

Benefits of technology

Effectively prevent the exposure of silicon particles, reduce gas production, improve the cycling performance of the battery cell, avoid excessive growth of silicon grains, and improve the structural stability and cycle life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581543A_ABST
    Figure CN119581543A_ABST
Patent Text Reader

Abstract

The invention provides a coated pre-lithium-silicon-oxygen negative electrode material as well as a preparation method and application thereof, and relates to the technical field of preparation of silicon negative electrode materials. The coated pre-lithium-silicon-oxygen negative electrode material comprises a pre-lithium-silicon-oxygen material, the interface stable layer is coated on the outer surface of the pre-lithium silica material; and the hydrophobic layer is coated on the outer surface of the interface stabilizing layer. The coated pre-lithium-silicon-oxygen negative electrode material disclosed by the invention can isolate silicon from being in contact with water and electrolyte, so that the silicon is prevented from reacting with hydroxyl ions to generate gas in a pulping process, and the cycle performance of a battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon negative electrode material preparation, and in particular to a coated pre-lithium silicon-oxygen negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, people have put forward higher and higher requirements for battery life, safety, fast charging and other performance. Silicon-based negative electrode materials are considered to be new high-performance lithium-ion battery negative electrode materials due to their advantages such as high specific capacity, good safety and abundant sources. With the development of high-capacity silicon-based negative electrode materials, surface modification and element doping have been widely used to improve material performance, among which pre-lithiation technology has a more significant improvement in the first efficiency and battery energy density.

[0003] However, the unstable factors accompanying the pre-lithiation process of silicon oxide materials lead to the exposure of nano-silicon, which makes the pre-lithiation silicon oxide materials easily react with hydroxide ions to produce gas during the slurrying process, affecting the quality of the subsequent coating process. In order to reduce the exposure of silicon, the surface of the pre-lithiation silicon oxide material is often modified by surface coating, but the existing coating method often requires sintering at 700℃ to 900℃, which will cause the silicon grains to grow excessively and the volume expansion effect is obvious, which is not conducive to the long cycle of the pre-lithiation silicon oxide negative electrode material. Summary of the invention

[0004] 1. Technical issues to be solved

[0005] In view of the deficiencies in the prior art, the present invention provides a coated pre-lithium silicon oxide negative electrode material and a preparation method and application thereof, which solves the technical problem that the prior coating method requires high-temperature sintering.

[0006] (II) Technical solution

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] In a first aspect, the present invention provides a coated pre-lithium silicon-oxygen negative electrode material, comprising:

[0009] Pre-lithium silicon-oxygen materials;

[0010] An interface stabilizing layer, which is coated on the outer surface of the pre-lithium silicon-oxygen material;

[0011] The hydrophobic layer is coated on the outer surface of the interfacial stabilizing layer.

[0012] The coated pre-lithium silicon-oxygen negative electrode material of the present invention comprises an interface stabilization layer and a hydrophobic layer. The interface stabilization layer and the hydrophobic layer isolate silicon in the pre-lithium silicon-oxygen material from contact with water and electrolyte, thereby preventing silicon from reacting with hydroxide ions to produce gas during pulping and improving the cycle performance of the battery cell.

[0013] Preferably, the coated pre-lithium silicon oxide negative electrode material satisfies at least one of the following conditions:

[0014] The interface stabilizing layer is obtained by calcining a water-soluble polymer, thereby realizing liquid-phase low-temperature carbon coating, and the coating effect is uniform and will not cause excessive growth of silicon grains, which is beneficial to the size control of silicon grains;

[0015] The hydrophobic layer is obtained by coating the hydrophobic material with a supercritical fluid method. The supercritical fluid coating method is used for coating. The supercritical fluid is used as a solvent. The hydrophobic material has a difference in solubility in the supercritical fluid. When the pressure is sharply reduced, the hydrophobic material is in a supersaturated state and rapidly nucleates and precipitates, forming a hydrophobic micronucleus sedimentation. The expanded airflow carries the hydrophobic micronucleus and collides with the silicon oxide material particles in the fluidized bed, producing uniform contact, thereby forming a uniform hydrophobic layer coating on the surface of the silicon oxide material fine particles. The supercritical fluid coating method will not cause any pollution to the product. The product has the advantages of high purity, uniform geometry, narrow particle size distribution, simple manufacturing process, and moderate operation, especially for heat-sensitive and structurally unstable processing. There is a clear advantage. This coating method can obtain high-quality coating of hydrophobic materials at low temperatures (100°C to 200°C), avoiding the problem of silicon grains growing up under multiple coatings.

[0016] The hydrophobic material of the present application forms a supercritical fluid under high pressure. The supercritical fluid expands rapidly and the temperature drops sharply when passing through the nozzle. The solvent and solute particles after the rapid expansion of the fluid are easy to separate quickly and thoroughly, and no solvent remains in the particles. There is no pollution to the product, which is a green process.

[0017] Preferably, the coated pre-lithium silicon oxide negative electrode material satisfies at least one of the following conditions:

[0018] The water-soluble polymer is selected from at least one of polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polymaleic anhydride, polyquaternary ammonium salt, and polyethylene glycol. Polyvinyl pyrrolidone (PVP) contains N element, and the generated interface stabilization layer includes nitrogen-doped carbon. The nitrogen-doped carbon connects the dispersed materials (dispersed conductive agent materials), thereby forming a 2D and 3D conductive network in the interface stabilization layer, thereby improving the conductivity of the negative electrode material.

[0019] The thickness of the interface stabilization layer is 1 to 20 nm.

[0020] The mass percentage of the water-soluble polymer to the mass percentage of the pre-lithium silicon-oxygen material is 1wt% to 6wt%;

[0021] The calcination temperature is 400-650°C.

[0022] Preferably, the coated pre-lithium silicon oxide negative electrode material satisfies at least one of the following conditions:

[0023] The hydrophobic material is selected from at least one of polystyrene, polyimide, aluminum phosphate, fluoride, and oxide;

[0024] The particle size D of the hydrophobic material 50 0.2~0.5um;

[0025] The amount of the hydrophobic material added is 0.1 wt% to 1 wt% of the pre-lithium silicon-oxygen material.

[0026] Preferably, the coated pre-lithium silicon oxide negative electrode material satisfies at least one of the following conditions:

[0027] The fluoride is selected from lithium fluoride and conductive glue;

[0028] The oxide is selected from aluminum oxide.

[0029] Preferably, the interface stabilization layer also includes a cross-linking agent obtained through a calcination process. The use of the cross-linking agent greatly enhances the coating strength, so that the interface stabilization layer is more firmly bonded to the surface of the pre-lithium silicon oxide material, avoiding excessive shear force during slurrying that may damage and peel off the interface stabilization layer and the hydrophobic layer structure, maintaining the structural integrity of the coated pre-lithium silicon oxide negative electrode material, and avoiding the exposure of silicon particles during the slurrying process to react with water to produce gas, thereby having a good effect in suppressing gas production and having excellent battery cycle performance.

[0030] Preferably, the gas production test method of the coated pre-lithium silicon oxide negative electrode material is as follows: the coated pre-lithium silicon oxide negative electrode material is mixed with a conductive agent and a binder to form a slurry, about 30 g of the homogenized slurry is sealed in an aluminum-plastic film bag, and allowed to stand at room temperature for 24 to 168 hours, and the gas production volume is tested by the drainage method; the slurry formula is a silicon, conductive agent, and binder mass ratio of (60 to 80): (10 to 20): (10 to 20), and the slurry mixing method is a semi-dry method.

[0031] Preferably, the electrical performance test method of the coated pre-lithium silicon oxide negative electrode material is: coating the coated pre-lithium silicon oxide negative electrode material on a current collector to form a pole piece, and then making a full battery together with a separator and an electrolyte to test the battery performance.

[0032] In a second aspect, the present invention provides a method for preparing the coated pre-lithium silicon oxide negative electrode material as described in the first aspect, comprising the following steps:

[0033] S1, dissolving the pre-lithium silicon-oxygen material, the water-soluble polymer, and the cross-linking agent in a solvent, evaporating the solvent, and calcining at 400-650° C. in a protective atmosphere to obtain a carbon-coated silicon-oxygen material;

[0034] S2. Mix the carbon-coated silicon-oxygen material and the hydrophobic material, and then coat them using a supercritical fluid method to obtain a coated pre-lithium silicon-oxygen negative electrode material.

[0035] Preferably, the preparation method satisfies at least one of the following conditions:

[0036] The cross-linking agent is selected from at least one of diisopropylbenzene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, polyurethane, styrene, and butadiene;

[0037] The added amount of the cross-linking agent accounts for 3% to 10% of the volume mass percentage of the pre-lithium silicon-oxygen material;

[0038] The solvent is selected from any one of alcohol and water;

[0039] The protective atmosphere is selected from any one of argon and helium.

[0040] Preferably, the specific process of supercritical fluid coating is:

[0041] The hydrophobic material is dissolved in a solvent and sent into a high-pressure tank to form a supercritical fluid, which is then rapidly expanded in a fluidized bed through a nozzle via a controlled heating pipeline. The particles in the fluidized bed are coated under the combined action of the expansion jet and the fluidizing gas, and the coating time is 60 minutes to 300 minutes. The temperature before expansion is controlled at 100°C to 200°C, and the particle size of the micronuclei formed by the hydrophobic material is controlled at 20 to 50 nm.

[0042] In a third aspect, the present invention provides an application of the coated pre-lithium silicon oxide negative electrode material as described in the first aspect in preparing a battery, wherein the battery comprises the coated pre-lithium silicon oxide negative electrode material, a current collector, a separator, and an electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 is a gas generation curve diagram of silicon negative electrode slurry of Example 1 and Comparative Example 1;

[0045] Figure 2 It is the soft pack battery cycle curve diagram of Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The embodiments of the present application provide a coated pre-lithium silicon oxide negative electrode material and a preparation method and application thereof, thereby solving the technical problem that the existing coating method requires high-temperature sintering.

[0048] The technical solution in the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0049] The present invention discloses a coated pre-lithium silicon-oxygen negative electrode material, in which the interface stabilization layer constructs an electrochemically stable interface between silicon and water, electrolyte, etc., and has good electrical conductivity; at the same time, in order to increase the coating strength and the adhesion between the interface stabilization layer and silicon, a cross-linking agent is added during coating to make the interface stabilization layer more firmly bonded to the surface of the silicon negative electrode, so as to prevent the excessive shear force of the dispersion disk during slurry mixing from destroying and peeling the structure of the interface stabilization layer, thereby maintaining the structural integrity and stability of the interface stabilization layer. Then, the surface of the hydrophobic layer is coated, and the coating is carried out by supercritical fluid method to achieve uniform coating of low-temperature ultrafine particles of hydrophobic materials such as oxides and fluorides. The coated pre-lithium silicon-oxygen negative electrode material prepared by the present invention has good structural stability, uniform and controllable coating, low coating temperature, and is conducive to controlling the growth of silicon grains. The interfacial stabilization layer and the hydrophobic layer form an effective synergistic effect, effectively preventing the exposure of silicon particles, thereby avoiding the reaction of the coated pre-lithium silicon oxide negative electrode material with hydroxide ions to produce gas during the slurrying process, solving the problem of gas production in the pre-lithium silicon oxide material slurry, ensuring the quality of the coating process, and improving the cycle performance of the battery cell.

[0050] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0051] Example 1

[0052] This embodiment provides a method for preparing a coated pre-lithium silicon-oxygen negative electrode material, comprising the following steps:

[0053] S1, the pre-lithiated silicon-oxygen material is filtered and washed with acetic acid and water in sequence, and finally dried at low temperature for standby use;

[0054] S2, add 30g of washed pre-lithium silicon-oxygen material, 5g of PVP material, and 1mL of diisopropylbenzene hydroperoxide into 100mL of alcohol, evaporate the alcohol completely after they are completely dissolved, and then calcine at 600°C for 6h under an argon protective atmosphere to obtain a carbon-coated silicon-oxygen material SiO / C composite material;

[0055] S3. Mix the SiO / C composite material with 0.1%wt of alumina material, and coat it by supercritical fluid method. The coating time is 60min, the temperature before expansion is controlled at 100°C, and the particle size of solute (hydrophobic material) micronucleus is controlled at 20nm to obtain a coated pre-lithium silicon oxide negative electrode material.

[0056] The prepared coated pre-lithium silicon-oxygen negative electrode material, conductive agent and binder are added to a slurry mixing tank, and slurry is mixed according to the ratio of silicon: ultrafine carbon powder (SP): single-walled carbon nanotube (SWCNT): polyacrylic acid (PAA) = 60:10:10:20, first dry mixing, then kneading, and then adjusting the viscosity; the solid content is controlled to be 15%, the viscosity is 8000mpas, and stirring is performed to obtain a uniformly dispersed silicon negative electrode slurry; about 30g of the homogenized silicon negative electrode slurry is taken and sealed in an aluminum-plastic film bag, and allowed to stand at room temperature for 7 days, and the gas production volume is tested by the drainage method. The gas production curve is shown in FIG. Figure 1 .

[0057] Example 2

[0058] This embodiment provides a coated pre-lithium silicon oxide negative electrode material, comprising the following steps:

[0059] S1, the pre-lithiated silicon-oxygen material is filtered and washed with trifluoroacetic acid, and then dried at low temperature for later use;

[0060] S2, dissolving 30g of the washed pre-lithium silicon-oxygen material, 10g of polyacrylamide material, and 3mL of cross-linking agent di-tert-butyl peroxide in deionized water, evaporating the water completely, and calcining at 500°C for 8h under an argon protective atmosphere to obtain a carbon-coated silicon-oxygen material SiO / C composite material;

[0061] S3. Mix the SiO / C composite material with 0.5 wt% of lithium fluoride material, and coat it by a supercritical fluid method to obtain a coated pre-lithium silicon oxide negative electrode material.

[0062] The coated pre-lithium silicon-oxygen negative electrode material, conductive agent, binder, etc. are added into a slurry mixing tank, and the slurry is mixed in the ratio of silicon: graphite: SP: SWCNT: PAA = 5: 88: 2: 0.1: 4.9. Dry mixing is first performed, then kneading, and then the viscosity is adjusted; the solid content is controlled to be 50%, the viscosity is 3500mpas, and the mixture is stirred to obtain a uniformly dispersed silicon negative electrode slurry, which is coated on the current collector, and the surface density is controlled to be 100g / m 2, and the ternary positive electrode is used to make a soft pack battery, and the cycle performance is tested. The results are shown in Figure 2 .

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 1 is that steps S2 and S3 are not included, and the washed pre-lithium silicon oxide material is used instead of the coated pre-lithium silicon oxide negative electrode material to mix with the conductive agent and the binder to prepare the silicon negative electrode slurry, and the rest is the same as Example 1. The gas production curve is shown in Figure 1 .

[0065] Figure 1 It can be seen that the gas production of the coated pre-lithium silicon oxide negative electrode material of the present invention after slurry mixing is only 1.5 mL after 7 days, while the gas production of the pre-lithium silicon oxide material of comparative example 1 after 7 days is 36.8 mL. The coated pre-lithium silicon oxide negative electrode material of the present invention can significantly reduce the gas production.

[0066] Comparative Example 2

[0067] The difference from Example 2 is that steps S2 and S3 are not included, and the washed pre-lithium silicon-oxygen material is used instead of the coated pre-lithium silicon-oxygen negative electrode material and the conductive agent, binder, etc. are added to the slurry tank to prepare the silicon negative electrode slurry. The other parts are the same as Example 2. The cycle performance results of the soft-pack battery are shown in Figure 2 .

[0068] Depend on Figure 2 It can be seen that the cycle life of the soft-pack battery of Example 2 is >1200 cycles, while the cycle life of the soft-pack battery of Comparative Example 2 is only 650 cycles. It can be seen that the coated pre-lithium silicon oxide negative electrode material of the present invention can significantly improve the cycle performance of the battery.

[0069] Comparative Example 3

[0070] The only difference between this comparative example and Example 1 is that S2 is not included, and the washed pre-lithiation silicon oxide material is used instead of the carbon-coated silicon oxide material SiO / C composite material to prepare the coated pre-lithiation silicon oxide negative electrode material. The rest is the same as Example 1, and the gas production of the silicon negative electrode slurry after 7 days is 10.5 mL.

[0071] Comparative Example 4

[0072] The only difference between this comparative example and Example 1 is that S3 is not included, and the silicon negative electrode slurry is prepared by using a carbon-coated silicon oxide material SiO / C composite material. The other aspects are the same as Example 1, and the gas production in 7 days is 15.5 mL.

[0073] In summary, the coated pre-lithium silicon-oxygen negative electrode material prepared by the present invention has a low coating temperature, which is conducive to controlling the growth of silicon grains. The interface stabilization layer and the hydrophobic layer form an effective synergistic effect, effectively preventing the silicon particles from being exposed, solving the problem of gas production in the pre-lithium silicon-oxygen material slurry, and greatly improving the battery cell cycle performance.

[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0075] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coated pre-lithium silicon-oxygen negative electrode material, characterized in that: include, Pre-lithium silicon-oxygen materials; An interface stabilizing layer, which is coated on the outer surface of the pre-lithium silicon-oxygen material; The hydrophobic layer is coated on the outer surface of the interfacial stabilizing layer.

2. The coated pre-lithium silicon-oxygen negative electrode material according to claim 1, characterized in that: The coated pre-lithium silicon oxide negative electrode material meets at least one of the following conditions: The interface stabilizing layer is obtained by calcining a water-soluble polymer; The hydrophobic layer is obtained by coating the hydrophobic material with a supercritical fluid method.

3. A coated pre-lithium silicon-oxygen negative electrode material according to claim 2, characterized in that: The coated pre-lithium silicon oxide negative electrode material meets at least one of the following conditions: The water-soluble polymer is selected from at least one of polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, polyvinyl alcohol, polymaleic anhydride, polyquaternary ammonium salt, and polyethylene glycol; The mass percentage of the water-soluble polymer to the mass percentage of the pre-lithium silicon-oxygen material is 1wt% to 6wt%; The calcination temperature is 400-650°C.

4. A coated pre-lithium silicon-oxygen negative electrode material according to claim 2, characterized in that: The coated pre-lithium silicon oxide negative electrode material meets at least one of the following conditions: The hydrophobic material is selected from at least one of polystyrene, polyimide, aluminum phosphate, fluoride, and oxide; The particle size D of the hydrophobic material 50 0.2~0.5um; The amount of the hydrophobic material added is 0.1 wt% to 1 wt% of the pre-lithium silicon-oxygen material.

5. A coated pre-lithium silicon-oxygen negative electrode material according to claim 4, characterized in that: The coated pre-lithium silicon oxide negative electrode material meets at least one of the following conditions: The fluoride is selected from lithium fluoride or conductive glue; The oxide is selected from aluminum oxide.

6. A coated pre-lithium silicon-oxygen negative electrode material according to claim 2, characterized in that: The interface stabilizing layer is also obtained by calcining a cross-linking agent.

7. A method for preparing the coated pre-lithium silicon oxide negative electrode material according to any one of claims 1 to 6, characterized in that: The steps include: S1, dissolving the pre-lithium silicon-oxygen material, the water-soluble polymer, and the cross-linking agent in a solvent, evaporating the solvent, and calcining at 400-650° C. in a protective atmosphere to obtain a carbon-coated silicon-oxygen material; S2. Mix the carbon-coated silicon-oxygen material and the hydrophobic material, and then coat them using a supercritical fluid method to obtain a coated pre-lithium silicon-oxygen negative electrode material.

8. The preparation method according to claim 7, characterized in that: The preparation method meets at least one of the following conditions: The cross-linking agent is selected from at least one of diisopropylbenzene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, polyurethane, styrene, and butadiene; The added amount of the cross-linking agent accounts for 3% to 10% of the volume mass percentage of the pre-lithium silicon-oxygen material; The solvent is selected from any one of alcohol and water; The protective atmosphere is selected from any one of argon and helium.

9. The preparation method according to claim 7, characterized in that: The supercritical fluid coating process comprises: The hydrophobic material is dissolved in a solvent and pressurized to form a supercritical fluid, which is then rapidly expanded to achieve coating, and the coating time is 60 to 300 minutes; the temperature before expansion is 100 to 200° C., and the micronuclei formed by the hydrophobic material have a particle size of 20 to 50 nm.

10. Use of the coated pre-lithium silicon-oxygen negative electrode material according to any one of claims 1 to 6 in preparing a battery, characterized in that: The battery comprises a coated pre-lithium silicon-oxygen negative electrode material, a current collector, a separator and an electrolyte.

Citation Information

Patent Citations

  • Silicon-carbon composite cathode material of pitaya-like structure and manufacturing method thereof

    CN110429272A

  • Treatment method of pre-lithiated SiOx negative electrode material

    CN112103480A

  • Pre-lithiated silicon-oxygen composite material, preparation method thereof, negative pole piece, battery and application of pre-lithiated silicon-oxygen composite material

    CN114975967A

  • Modified high-first-effect silicon-oxygen negative electrode material and preparation method thereof

    CN115117320A

  • Modified pre-lithiated silica material, preparation method and application thereof and lithium ion battery

    CN116053453A